2022
DOI: 10.1002/ibra.12028
|View full text |Cite
|
Sign up to set email alerts
|

Differences between cultured cortical neurons by trypsin and papain digestion

Abstract: The objective of this study was to compare the efficiency of trypsin and papain in neuronal digestion and determine which enzyme is more efficient. Cortical tissues were obtained from Sprague-Dawley (SD) rats. According to the different digestive enzymes, the samples were divided into the trypsin group and the papain group. After being digested by each of the two enzymes, cortical neurons were collected from the samples. Then, the morphology of the cortical neurons was determined. Moreover, the cortical neuron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Studies have compared the digestion efficiency and culture effect of TP and papain, and found that it is comparable to that of papain. Compared with the papain group, the TP group had more cortical neurons, larger cell bodies, longer axonal lengths, and fewer impurities 15 …”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Studies have compared the digestion efficiency and culture effect of TP and papain, and found that it is comparable to that of papain. Compared with the papain group, the TP group had more cortical neurons, larger cell bodies, longer axonal lengths, and fewer impurities 15 …”
Section: Discussionmentioning
confidence: 91%
“…Compared with the papain group, the TP group had more cortical neurons, larger cell bodies, longer axonal lengths, and fewer impurities. 15 …”
Section: Discussionmentioning
confidence: 99%
“…Enzymatic dissociation is the method of choice for preparing primary cultures from tissue and has been studied in detail to ensure the perfect balance between the optimal isolation of cells and minimal artificial modification. For instance, previous studies have explored the effects of such enzymatic-based isolation protocols in various cell types and tissues: satellite stem cells from muscle tissue (Miersch et al, 2018), mesenchymal stem/stromal cell isolation from umbilical cord tissue (Taghizadeh et al, 2018), adipose-derived stem cells (Koellensperger et al, 2022), chondrocytes from cartilage (Hidvegi et al, 2006), T cells from spleen and lung tissue (Liu et al, 2018) and neurons and glial cells from brain cortex (Panchision et al, 2007;Mattei et al, 2020;Hu et al, 2022). Similarly, O'Flanagan et al reported that the collagenase digestion for dissociating solid tumor tissues triggers a stress response that alters the transcriptome of the isolated cancer cells (O'Flanagan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%